ABLUTION WORKSTATIONS DESIGN FOR PERSON WITH PHYSICAL DISABILITIES IN MALAYSIA - Siti Zawiah MD Dawal; Mirta W; Nur Syahirah A; Muhammad Suhairi A (Malaysian Journal of Public Health Medicine, 2020)
An investigation on ablution workstations design for person with disabilities has been carried out in this study. The focused were on wheelchair user or person with lower-limb impairment in Malaysia. The objective of this research is to determine the most suitable ablution workstation for person with disabilities. One hundred wheelchair users which include 74 males and 26 females participated in the study. The findings highlighted that the most suitable and preferred ablution workstation for person with disabilities is a separate design for washing hands and legs. The results also indicated that the noteworthy body parts that should be enhanced are arms, neck, trunk, and legs. Therefore, it can be concluded that it is important to design an ablution workstation with correct anthropometric dimensions referring to the population under investigation taking into account their preferences and disabilities limitation. Thus, the innovation will bring equality between people with disabilities and physically normal people in future facilities design. The workstation will become one of the worthy social contributions to the population of Muslim disabilities especially in Malaysia.